Experimental investigation of desiccant dehumidification with four different combinations of silica gel desiccant wheel on indoor air quality - Kishor S. Rambhad; Pramod V. Walke; Vednath P. Kalbande; Manoj A. Kumbhalkar; Vivek W. Khond; Yogesh Nandanwar; Man Mohan; Rahul Jibhakate (SN Applied Sciences, 2023)
Abstract Indoor air quality (IAQ) describes the air quality within buildings and other structures, particularly concerning how it affects the health and comfort of building inhabitants. Your likelihood of experiencing indoor health issues can be decreased by being aware of and controlling common indoor contaminants. In addition to maintaining indoor relative humidity at or below 65%, The American Society of Heating, Refrigerating, and Air-Conditioning Engineers (ASHRAE) recommends temperatures between 21 and 26 °C in the summer and 20–24 °C in the winter. The EPA advises using humidity levels between 30 and 60% to stop mold from growing. Silica gel, lithium chloride, and molecular sieves 5A are excellent for dehumidification due to their strong moisture adsorption capability and potential for regeneration. Choosing the right desiccant depends on factors like adsorption capacity, pore size, and chemical compatibility, which are crucial for dehumidification applications and environments. This study compares the performance of silica gel desiccant wheels with three additional composite materials for air dehumidification, which is unusual in this work because very few studies of these combinations have been provided. For all desiccant wheels, the various operating parameters of the needed dehumidification process have been investigated and compared. For adsorption and regeneration rate, the performance of three different composite desiccant wheels was examined and compared experimentally. This experimental evaluation reveals that the composite desiccant wheel (silica gel-lithium chloride-molecular sieve 5A) has a higher adsorption and regeneration rate than others. When a composite desiccant wheel made from silica gel-lithium chloride, silica gel-molecular sieve 5A, and silica gel-lithium chloride-molecular sieve 5A was compared to the performance of a silica gel desiccant wheel, the percentage improvements in adsorption rate were 34.99%, 43.58%, and 85.5%, and the percentage increases in regeneration rate were 5.65%, 7.08%, and 14%.